Childhood bullying, paranoid thinking, and the misappraisal of social threat: trouble at school - Jack, Alexander H.; Egan, Vincent (Springer, 2017)
Background:Experiences of bullying predict the development of paranoia in school-age adolescents. While many instances of psychotic phenomena are transitory, maintained victimization can lead to increasingly distressing paranoid thinking. Furthermore, paranoid thinkers perceive threat in neutral social stimuli and are vigilant for environmental risk. Aims:The present paper investigated the association between different forms of bullying and paranoid thinking, and the extent to which school-age paranoid thinkers overestimate threat in interpersonal situations. Methods: Two hundred and thirty participants, aged between eleven and fourteen, were recruited from one secondary school in the UK. Participants completed a series of questionnaires hosted on the Bristol Online Survey tool. All data were collected in a classroom setting in quiet and standardized conditions. Results: A significant and positive relationship was found between experiences of bullying and paranoid thinking: greater severity of bullying predicted more distressing paranoid thinking. Further, paranoid thinking mediated the relationship between bullying and overestimation of threat in neutral social stimuli. Conclusion: Exposure to bullying is associated with distressing paranoid thinking and subsequent misappraisal of threat. As paranoid thinkers experience real and overestimated threat, the phenomena may persist.